Профессиональная деятельность казахских специалистов в XIX веке - Айтмухамбетов, А.А.; Молдабаева, С.А. (My University, 2016)
In this article professional activity of the Kazakh specialists is lighted up 19 centuries on territory of the Russian empire. The analysis of basic activity of specialists is given in the conditions of colonization of edge.
Keywords: Kazakh specialists; activity; profession; speciality